Artificial diamond surface self-gradient alloying method

By self-gradient alloying treatment on the surface of artificial diamond, a carbonized protective layer and a tool matrix wetting layer are formed, which solves the problem of poor bonding force between diamond and matrix, and improves the cutting efficiency and service life of the tool.

CN119114937APending Publication Date: 2024-12-13ZHONGNAN DIAMOND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411210719.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the bonding force of ultrahard abrasive diamond with cutting tools and polishing abrasive base materials is poor, the coating processing cycle is long and the cost is high, resulting in low tool use efficiency.

Method used

By using the artificial diamond surface self-gradient alloying method, the inert powder with a specific particle size is mixed with metal powders such as titanium and chromium, and sintered at high temperature under vacuum to form a carbonized protective metal layer and a tool matrix wet metal layer, realizing one-time It can improve binding force and inhibit graphitization and oxidation corrosion of diamond particles.

Benefits of technology

The self-gradient film layer is formed in a sintering reaction, which improves the strength and binding force of diamond particles, reduces costs, increases tool blade time, and improves cutting efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114937A_ABST
    Figure CN119114937A_ABST
Patent Text Reader

Abstract

The invention discloses an artificial diamond surface self-gradient alloying method which comprises the following steps: step 1, prefabricating alloy powder which is a mixture of inert micro powder, first metal powder and second metal powder; fully wetting the surface of the artificial diamond by using a wetting agent; 2, alloy powder and the wetted artificial diamond are mixed, and material powder is obtained; 3, uniformly placing the material powder in a high-temperature-resistant container, and standing; 4, the high-temperature-resistant container is put into a vacuum sintering furnace for calcination, a system is naturally cooled to the room temperature after calcination is completed, and a material is obtained; and step 5, carrying out ball milling on the material, screening out residues on the surface of the material after ball milling, and cleaning and drying the material. The method can protect a metal layer and a tool matrix infiltration metal layer through one-time carbonization, spontaneously form a concentration gradient metal film, has the characteristics of low melting point and high hardness, can accelerate the exposure of an artificial diamond tool, and achieves the purpose of improving the cutting efficiency of the tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of superhard material functionalization and relates to a method for self-gradient alloying of artificial diamond surface. Background Art

[0002] Superabrasive diamond has important applications in cutting tools, polishing tools, etc. due to its ultra-high hardness and excellent wear resistance. Due to the high interface energy between superabrasives and the base materials of cutting tools and polishing tools, the bonding force between superabrasives and the base materials of cutting tools and polishing tools is very poor. In order to enhance the bonding force between superabrasive diamond and the base materials of cutting tools and polishing tools, diamonds are usually plated with carbide metal layers such as Ti and Cr for protection and then coated with Ni, Fe, Cu, etc., and processed into tools for use. Carbide metal layers such as Ti and Cr prevent diamond oxidation and graphitization, and metal layers such as Ni, Fe, Cu are easy to combine with the metal base of the tool to increase the bonding force.

[0003] The current coating adopts a secondary coating method. First, titanium is plated on the outside of the diamond particles, and then nickel is electroplated for coating. The titanium layer is a bonding protection layer, and the nickel layer is a base metal infiltration welding layer. This method has a long processing cycle and is costly and labor-intensive. In addition, the metal layer on the outside of the diamond particles exhibits strong toughness and is extremely difficult to break and shatter on a macro scale. After being used in tool abrasives, the speed at which the diamond particles in the tool abrasives are exposed from the metal layer is slow, causing the tool head grinding disc to become dull and the cutting and polishing efficiency to be very low during the initial use of the tool abrasives. Only after long-term and multiple uses will the diamond particles come into direct contact with the workpiece, and the tool abrasives will then have a higher sharpness. Summary of the invention

[0004] The purpose of the present invention is to provide a method for self-gradient alloying of the surface of artificial diamond, which solves the problems of poor bonding between diamond and substrate and long coating cycle existing in the prior art.

[0005] The technical solution adopted by the present invention is a method for self-gradient alloying of the surface of artificial diamond, comprising the following steps:

[0006] Step 1: prefabricate alloy powder, which is a mixture of inert micropowder, first metal powder and second metal powder; wet the artificial diamond, mix the wetting agent with the artificial diamond and stir for 5-10 minutes;

[0007] Step 2: Stirring the alloy powder and the wetted artificial diamond to obtain a powder;

[0008] Step 3: Place the powder evenly in a high temperature resistant container and let it stand for 8-24 hours;

[0009] Step 4: placing the high temperature resistant container into a vacuum sintering furnace for calcination, and after the calcination is completed, the system is naturally cooled to room temperature to obtain a material;

[0010] Step 5: ball mill the material, screen out the residue on the surface of the material after ball milling, and wash and dry the material.

[0011] The present invention is also characterized in that:

[0012] The inert micro powder is one or more of silicon powder and aluminum oxide powder, and its particle size is 20-200 μm.

[0013] The first metal powder is one or more of titanium, chromium, vanadium and tungsten, and its particle size is 10-100 μm.

[0014] The second metal powder is one or more of nickel, iron and copper, and its particle size is 10-100 μm.

[0015] The mass ratio of the inert micro powder to the first metal powder is 1:(0.6-1), and the mass ratio of the inert micro powder to the second metal powder is 1:(1.2-2).

[0016] The preparation conditions of the alloy powder are as follows: placing the inert micropowder, the first metal powder and the second metal powder in a mixer at a rotation speed of 35-45 r / min and a mixing time of 10-15 min.

[0017] The wetting agent is artificial diamond. When the particle size of artificial diamond is 70 / 80 or finer, the volume ratio of the mass of artificial diamond to the wetting agent is 1: (0.067-0.1) g / ml; when the particle size of artificial diamond is 60 / 70 or coarse, the volume ratio of the mass of artificial diamond to the wetting agent is 1: (0.05-0.083) g / ml.

[0018] Specifically, when the particle size of the artificial diamond is 70 / 80 or finer, the mass ratio of the artificial diamond to the alloy powder is 1:(2-2.4); when the particle size of the artificial diamond is 60 / 70 or coarse, the mass ratio of the artificial diamond to the alloy powder is 1:(1.6-2).

[0019] The stirring condition is specifically to mix the alloy powder and the artificial diamond and stir for 10-15 minutes.

[0020] The calcination in the vacuum sintering furnace is specifically carried out under a vacuum of no more than 10 -1 Pa, heat to 800-1000℃ and keep warm for 240-360min.

[0021] The beneficial effects of the present invention are:

[0022] 1. The method for self-gradient alloying of the surface of artificial diamond of the present invention comprises the following steps: mixing inert micropowder of a specific particle size with metal powders such as titanium and chromium that can form stable carbides with artificial diamond and metal powders such as Ni and Cu that can be infiltrated with a matrix in a specific ratio, and then subjecting the mixture to high-temperature sintering treatment under a vacuum state, thereby achieving one-time completion of the carbonization protection metal layer and the tool matrix infiltrated metal layer, inhibiting the graphitization and oxidative corrosion of artificial diamond particles under high temperature conditions, improving the strength of artificial diamond particles, improving the bonding between artificial diamond and the matrix, and enhancing the holding force of the binder on the abrasive particles.

[0023] 2. The self-gradient alloying method of the artificial diamond surface of the present invention has a low melting point and high hardness, which can increase the cutting speed of the artificial diamond tool, thereby achieving the purpose of improving the cutting efficiency of the tool. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of a titanium-nickel self-gradient diamond coating product of Example 2 of the self-gradient alloying of the surface of artificial diamond of the present invention;

[0025] Figure 2 This is a SEM scan picture of the cross section of the titanium-nickel self-gradient diamond after crushing in Example 2 of the self-gradient alloying of the artificial diamond surface of the present invention;

[0026] Figure 3 This is an EDS element content line analysis diagram of the cross section of the titanium-nickel self-gradient diamond metal film in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The method for self-gradient alloying of artificial diamond surface comprises the following steps:

[0029] Step 1: prefabricating alloy powder, wherein the alloy powder is a mixture of inert micropowder, a first metal powder and a second metal powder, wherein the inert micropowder is one or more of silicon powder and aluminum oxide powder, and the particle size thereof is 20-200 μm, wherein the purity of silicon powder and aluminum oxide powder is 99.9%, the first metal powder is one or more of titanium, chromium, vanadium and tungsten, and the particle size thereof is 10-100 μm, wherein the purity of titanium, chromium, vanadium and tungsten is 99.9%, and the second metal powder is one or more of nickel, iron and copper, and the particle size thereof is 10-100 μm, wherein the purity of nickel, iron and copper is 99.9%; the mass ratio of the inert micropowder to the first metal powder is 1:(0.6-1), and the mass ratio of the inert micropowder to the second metal powder is 1:(1.2-2), and the inert micropowder, the first metal powder and the second metal powder are placed in a mixer, the rotation speed is 35-45 r / min, and the mixing time is 10-15 min;

[0030] The artificial diamond is wetted, and the wetting agent and the artificial diamond are mixed and stirred for 5-10 minutes, wherein the wetting agent is alcohol. The wetting is specifically to take the artificial diamond. When the particle size of the artificial diamond is 70 / 80 or finer, the volume ratio of the mass of the artificial diamond to the wetting agent is 1: (0.067-0.1) g / ml; when the particle size of the artificial diamond is 60 / 70 or coarse, the volume ratio of the mass of the artificial diamond to the wetting agent is 1: (0.05-0.083) g / ml.

[0031] Step 2: Stir the alloy powder with the wetted artificial diamond to obtain a powder. When the particle size of the artificial diamond is 70 / 80 or finer, the mass ratio of the artificial diamond to the alloy powder is 1:(2-2.4); when the particle size of the artificial diamond is 60 / 70 or coarse, the mass ratio of the artificial diamond to the alloy powder is 1:(1.6-2). Mix the alloy powder and the artificial diamond and stir for 10-15 minutes.

[0032] Step 3: Place the powder evenly in a high temperature resistant container and let it stand for 8-24 hours;

[0033] Step 4: Place the high temperature resistant container in a vacuum sintering furnace for calcination. -1 Pa, heating to 800-1000°C, keeping warm for 240-360 minutes, and naturally cooling the system to room temperature after calcination to obtain the material;

[0034] Step 5: ball mill the material, screen out the residue on the surface of the material after ball milling, and wash and dry the material.

[0035] Example 1

[0036] First, alloy powder is premade, and silicon powder with a purity of 99.9% and a particle size of 180μm, metal chromium powder of 10μm, and metal iron powder of 10μm are selected to mix and prepare alloy powder, wherein the mass ratio of silicon powder to metal chromium powder is 1:1, and the mass ratio of silicon powder to metal iron powder is 1:2. The mixture is placed in a mixer for mixing. The speed of the mixer is 40r / min, and the mixing time is 35min. After mixing, the mixture is taken out for use.

[0037] Wetting the artificial diamond, selecting the artificial diamond with the brand ZND2140 and the particle size of 70 / 80, weighing 600g of artificial diamond, mixing the artificial diamond with 40ml of alcohol for 7min, so that the surface of the artificial diamond is fully soaked. Mix the fully soaked artificial diamond with 1200g of alloy powder, stirring and mixing for 10min, evenly placing the fully mixed powder in a high temperature resistant container, standing for 8h, and placing the high temperature resistant container in a vacuum sintering furnace for heating after standing. The specific heating conditions are heating to 860℃ and keeping warm for 280min when the vacuum is evacuated to 0.1Pa. After calcination, it is naturally cooled, and the residue on the surface of the material is screened out after the material is cooled to room temperature, and the material is cleaned and dried to obtain chromium-iron self-gradient diamond.

[0038] Example 2

[0039] First, alloy powder is prefabricated. Silicon powder with a purity of 99.9% and a particle size of 200 μm, metal titanium powder of 30 μm, and metal nickel powder of 20 μm are selected to mix and prepare alloy powder, wherein the mass ratio of silicon powder to metal titanium powder is 1:0.6, and the mass ratio of silicon powder to metal nickel powder is 1:1.2. The mixture is placed in a mixer for mixing. The speed of the mixer is 35 r / min, and the mixing time is 40 min. After mixing, the mixture is taken out for standby use.

[0040] Wet the artificial diamond, select the artificial diamond with the brand ZND2040 and the particle size of 80 / 100, weigh 600g of artificial diamond, mix the artificial diamond with 50ml of alcohol for 9 minutes, so that the surface of the artificial diamond is fully soaked. Mix the fully soaked artificial diamond with 1380g of alloy powder, stir and mix for 15 minutes, evenly place the fully mixed powder in a high-temperature resistant container, let it stand for 10 hours, and then put the high-temperature resistant container into a vacuum sintering furnace for heating. The specific heating conditions are to heat to 800℃ and keep warm for 270 minutes when the vacuum is evacuated to 0.05Pa. After calcination, cool it naturally. After the material is cooled to room temperature, screen out the residue on the surface of the material, and wash and dry the material to obtain titanium-nickel self-gradient diamond. The schematic diagram of the titanium-nickel self-gradient diamond coating product is shown as follows Figure 1 shown.

[0041] like Figure 2 As shown in Figure 1, it can be clearly seen that the diamond layer and metal layer of the titanium-nickel self-gradient diamond are Figure 3As shown in the figure, it can be seen that the ordinate is the content, and the abscissa is from the metal layer to the diamond layer from A to B. Through the EDS element content line analysis of the cross section of the titanium-nickel self-gradient diamond metal film, it can be obtained that there are more titanium and nickel in the periphery of the film layer, the titanium content is higher near the diamond transition layer, the nickel content is reduced, the diamond layer is pure carbon element, and the film layer obviously forms a gradient. This method can form a self-gradient film layer through a single sintering reaction, and a titanium carbide protective layer with a high titanium content is formed near the diamond. The high nickel content in the periphery can effectively combine with the substrate, increase the bonding force, reduce the cost, and play a protective role.

[0042] Example 3

[0043] Firstly, alloy powder is prefabricated, and silicon powder with a purity of 99.9% and a particle size of 100 μm, metal vanadium powder of 70 μm, and metal copper powder of 50 μm are selected to mix and prepare alloy powder, wherein the mass ratio of silicon powder to metal vanadium powder is 1:1, and the mass ratio of silicon powder to metal copper powder is 1:1.3. The mixture is placed in a mixer for mixing. The speed of the mixer is 40 r / min, and the mixing time is 35 min. After mixing, the mixture is taken out for standby use.

[0044] Wetting the artificial diamond, selecting the artificial diamond with the brand ZND2040 and the particle size of 100 / 120, weighing 600g of artificial diamond, mixing the artificial diamond with 60ml of alcohol for 6min, so that the surface of the artificial diamond is fully soaked. The fully soaked artificial diamond is mixed with 1440g of alloy powder, stirring and mixing for 15min, and the fully mixed powder is evenly placed in a high-temperature resistant container, and the standing time is 15h. After standing, the high-temperature resistant container is placed in a vacuum sintering furnace for heating. The specific heating conditions are heating to 850℃ and keeping warm for 240min when the vacuum is evacuated to 0.01Pa. After calcination, it is naturally cooled, and the surface residue of the material is screened out after the material is cooled to room temperature, and the material is cleaned and dried to obtain vanadium copper self-gradient diamond.

[0045] Example 4

[0046] First, alloy powder is prefabricated, and aluminum oxide powder with a purity of 99.9% and a particle size of 50 μm, metal chromium powder of 50 μm, and metal iron powder of 60 μm are selected and mixed to prepare alloy powder, wherein the mass ratio of silicon powder to metal chromium powder is 1:0.65, and the mass ratio of silicon powder to metal iron powder is 1:1.8. The mixture is placed in a mixer for mixing. The speed of the mixer is 35 r / min, and the mixing time is 10 min. After mixing, the mixture is taken out for use.

[0047] Wetting the artificial diamond, selecting the artificial diamond with the brand ZND2140 and the particle size of 60 / 70, weighing 600g of artificial diamond, mixing the artificial diamond with 45ml of alcohol for 10min, so that the surface of the artificial diamond is fully soaked. The fully soaked artificial diamond is mixed with 960g of alloy powder, stirring and mixing for 15min, and the fully mixed powder is evenly placed in a high-temperature resistant container, and the standing time is 22h. After standing, the high-temperature resistant container is placed in a vacuum sintering furnace for heating. The specific heating conditions are heating to 1000℃ and keeping warm for 320min when the vacuum is evacuated to 0.08Pa. After calcination, it is naturally cooled. After the material is cooled to room temperature, the surface residue of the material is screened out, and the material is cleaned and dried to obtain chromium-iron self-gradient diamond.

[0048] Example 5

[0049] First, alloy powder is prefabricated. Silicon powder with a purity of 99.9% and a particle size of 150 μm, metal titanium powder with a particle size of 100 μm, and metal nickel powder with a particle size of 90 μm are selected and mixed to prepare alloy powder. The mass ratio of silicon powder to metal titanium powder is 1:0.75, and the mass ratio of silicon powder to metal nickel powder is 1:2. The mixture is placed in a mixer for mixing. The speed of the mixer is 40 r / min, and the mixing time is 40 min. After mixing, the mixture is taken out for standby use.

[0050] Wetting the artificial diamond, selecting the artificial diamond with the brand ZND2110 and the particle size of 60 / 70, weighing 600g of artificial diamond, mixing the artificial diamond with 50ml of alcohol for 10min, so that the surface of the artificial diamond is fully soaked. The fully soaked artificial diamond is mixed with 1080g of alloy powder, stirring and mixing for 12min, and the fully mixed powder is evenly placed in a high-temperature resistant container, and the standing time is 24h. After standing, the high-temperature resistant container is placed in a vacuum sintering furnace for heating. The specific heating conditions are heating to 1000℃ and keeping warm for 340min when the vacuum is evacuated to 0.07Pa. After calcination, it is naturally cooled, and the surface residue of the material is screened out after the material is cooled to room temperature, and the material is cleaned and dried to obtain titanium-nickel self-gradient diamond.

[0051] Example 6

[0052] Firstly, alloy powder is prefabricated, and silicon powder with a purity of 99.9% and a particle size of 20μm, metal tungsten powder of 90μm, and metal copper powder of 100μm are selected to mix and prepare alloy powder, wherein the mass ratio of silicon powder to metal tungsten powder is 1:0.9, and the mass ratio of silicon powder to metal copper powder is 1:1.55. The mixture is placed in a mixer for mixing. The speed of the mixer is 30r / min, and the mixing time is 30min. After mixing, the mixture is taken out for use.

[0053] Wetting the artificial diamond, select the artificial diamond with the brand ZND2240 and the particle size of 35 / 40, weigh 600g of artificial diamond, mix the artificial diamond with 30ml of alcohol for 5min, and fully soak the surface of the artificial diamond. Mix the fully soaked artificial diamond with 1200g of alloy powder, stir and mix for 13min, evenly place the fully mixed powder in a high-temperature resistant container, let it stand for 20h, and then put the high-temperature resistant container into a vacuum sintering furnace for heating. The specific heating conditions are to heat to 950℃ and keep warm for 360min when the vacuum is evacuated to 0.09Pa. After calcination, cool it naturally, and screen out the residue on the surface of the material after the material cools to room temperature, and wash and dry the material to obtain tungsten-copper self-gradient diamond.

[0054] In the method of the present invention, after the surface of the artificial diamond is fully wetted, gold powder is mixed to make the surface fully adhere to the alloy powder, wherein the carbide metal in the alloy powder easily and first reacts with the artificial diamond to form a carbide protective layer, and spontaneously forms a concentration gradient metal film during high-temperature vacuum sintering. The concentration of the carbide metal gradually decreases from the inside to the outside, and the concentration of the tool matrix infiltrating metal gradually increases. The carbide layer inhibits the graphitization and oxidative corrosion of the artificial diamond particles under high temperature conditions. The tool matrix infiltrating layer improves the combination of the artificial diamond and the matrix and enhances the holding force of the binder on the abrasive particles. The self-gradient alloy has a low melting point and high hardness, and can accelerate the cutting of the artificial diamond tool, thereby achieving the purpose of improving the tool cutting efficiency.

Claims

1. A method for self-gradient alloying of artificial diamond surface, characterized in that: The following steps are involved: Step 1: prefabricate alloy powder, wherein the alloy powder is a mixture of inert micropowder, first metal powder and second metal powder; wet the artificial diamond, mix the wetting agent with the artificial diamond and stir for 5-10 minutes; Step 2: stirring the alloy powder and the wetted artificial diamond to obtain a powder; Step 3: Place the powder evenly in a high temperature resistant container and let it stand for 8-24 hours; Step 4: placing the high temperature resistant container into a vacuum sintering furnace for calcination, and after the calcination is completed, the system is naturally cooled to room temperature to obtain a material; Step 5: ball milling the material, sieving out the residue on the surface of the material after ball milling, and washing and drying the material.

2. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The inert micro powder is one or both of silicon powder and aluminum oxide powder, and the particle size thereof is 20-200 μm.

3. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The first metal powder is one or more of titanium, chromium, vanadium and tungsten, and has a particle size of 10-100 μm.

4. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The second metal powder is one or more of nickel, iron and copper, and has a particle size of 10-100 μm.

5. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The mass ratio of the inert micropowder to the first metal powder is 1:(0.6-1), and the mass ratio of the inert micropowder to the second metal powder is 1:(1.2-2).

6. The method for self-gradient alloying of artificial diamond surface according to claim 5, characterized in that: The preparation conditions of the alloy powder are specifically as follows: placing the inert micropowder, the first metal powder and the second metal powder in a mixer, with a rotation speed of 35-45 r / min and a mixing time of 10-15 min.

7. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The wetting is specifically to take artificial diamond. When the particle size of the artificial diamond is 70 / 80 or finer, the volume ratio of the mass of the artificial diamond to the wetting agent is 1: (0.067-0.1) g / ml; when the particle size of the artificial diamond is 60 / 70 or coarse, the volume ratio of the mass of the artificial diamond to the wetting agent is 1: (0.05-0.083) g / ml.

8. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: Specifically, when the particle size of the artificial diamond is 70 / 80 or finer, the mass ratio of the artificial diamond to the alloy powder is 1:(2-2.4); when the particle size of the artificial diamond is 60 / 70 or coarse, the mass ratio of the artificial diamond to the alloy powder is 1:(1.6-2).

9. The method for self-gradient alloying of the surface of artificial diamond according to claim 8, characterized in that: The stirring condition is specifically to mix the alloy powder and the artificial diamond and stir for 10-15 minutes.

10. The method for self-gradient alloying of artificial diamond surface according to claim 1, characterized in that: The calcination in the vacuum sintering furnace is specifically carried out under vacuum to a temperature not greater than 10 -1 Pa, heat to 800-1000℃ and keep warm for 240-360min.